EFFORTS TO IMPROVE THE QUALITY OF THE COMMUNITY AS HUMAN RESOURCES IN THE CREATIVE INDUSTRY OF KWALA SERAPUH VILLAGE, LANGKAT - Andika, Rindi; Sari, Pipit Buana; Faried, Annisa Ilmi; Siregar, Deena Nikita (Proceeding International Seminar of Islamic Studies, 2024)
The creative industry is one of the important sectors in the Indonesian economy, including in villages. The village creative industry has the potential to improve the welfare of rural communities. However, the development of village creative industries requires adequate community quality, both in terms of skills, knowledge, and attitudes. This study aims to analyze efforts to improve the quality of the community as human resources in the creative industry of Kuala Serapuh village, Langkat. This research uses qualitative methods with a case study approach. The research data was collected through interviews, observations, and documentation The sample size was 50 respondents. The results showed that efforts to improve the quality of the community as human resources in the creative industry of Kuala Serapuh village were carried out through various ways, including: 1) training and education of skills and knowledge related to the creative industry, 2) increasing public access to information and technology and 3) forming a creative and innovative work culture. These efforts have had a positive impact on improving the quality of the community as human resources in the creative industry of Kwala Serapuh village. This is shown by the increasing skills, knowledge, and attitudes of the community in developing the village's creative industry.